If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + 8 = 3m Reorder the terms: 8 + 2m = 3m Solving 8 + 2m = 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 8 + 2m + -3m = 3m + -3m Combine like terms: 2m + -3m = -1m 8 + -1m = 3m + -3m Combine like terms: 3m + -3m = 0 8 + -1m = 0 Add '-8' to each side of the equation. 8 + -8 + -1m = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1m = 0 + -8 -1m = 0 + -8 Combine like terms: 0 + -8 = -8 -1m = -8 Divide each side by '-1'. m = 8 Simplifying m = 8
| 0.3r-2.8=3.2-0.2r | | 121b^2+12=156 | | 8.6=2.1-13y | | 2.4-5.1=4x-8.3 | | 4+5y=-21 | | 19.27(s+w)=100 | | 0.33333333333333a=0.33333333333333 | | 9(6+2x)=-(2-4x) | | -4(5-5)+3n= | | -(9x-4)=-5 | | T(9.69+w)=100 | | 120-4(3(-2+3)+5)= | | 2x^2+2y^2-324=0 | | (2x+9)(7x-8)=0 | | 8n^2+4=1156 | | Log(-2a)=log(7-4a) | | 4(x+2)-x=20 | | 9x+6=-6 | | 30x-10=31x | | 5m-3m=1+9 | | 1-4n+6+4=-7n+5 | | 5n+4n=32 | | y-3=-1(x-(-6)) | | 17+7=8x | | 8-h(2h)=72 | | (1-2)ym=2 | | 4-3(3-7x)=0 | | 2x+2y=324 | | 9.58(s-w)=100 | | u^2-3uv-40v^2= | | 6y=5x-30 | | (5+2x)(8-3x)=0 |